Marking time: art in the age of mass incarceration - Fleetwood, Nicole R. (Harvard University Press, 2020)
Carceral aesthetics: penal space, time, and matter -- State goods: clandestine practices and prison art collectives -- Captured by the frame: photographic studies of prisoners -- Interior subjects: portraits by incarcerated ̜̜artists -- Fraught imaginaries: collaborative art in prison -- Art in solitary confinement -- Posing in prison: family photographs, practices of belonging, and carceral landscapes.